Penyelesaian Tuntutan Sisa Hak Pesangon Pekerja Berdasarkan Kesepakatan : Analisis Pemutusan Hubungan Kerja pada PT. Nusa Halmahera Minerals - Hansed Pither Lasa; Sufiarina Sufiarina; Riana Wulandari (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Termination of employment is one of the most common occurrences in industrial relations. In practice, the implementation of workers' rights after termination, particularly those related to severance pay, does not always proceed in accordance with applicable legal provisions or mutually agreed terms. This study aims to analyze the settlement of remaining severance pay claims based on an agreement between the workers and PT. Nusa Halmahera Minerals. This study uses a normative juridical method with a Data was obtained through literature studies, legislation, and mutual agreement documents. The results of the study show that there are delays and inconsistencies in the implementation of severance pay as stated in the mutual agreement. The settlement was mostly non-litigious through mediation at the Manpower Office, but did not result in the full fulfillment of rights. This shows the weak bargaining position of workers in the implementation of collective labor agreements, as well as the need to strengthen legal mechanisms for sanctions against companies that fail to fulfill their obligations.